Comparative electron microscopy particle sizing of TiO2 pigments: sample preparation and measurement - Theissmann, Ralf; Drury, Christopher; Rohe, Markus; Koch, Thomas; Winkler, Jochen; Pikal, Petr (Beilstein Journal of Nanotechnology, 2024)
Titanium dioxide (TiO2) pigment is a non-toxic, particulate material in widespread use and found in everyone’s daily life. The particle size of the anatase or rutile crystals are optimised to produce a pigment that provides the best possible whiteness and opacity. The average particle size is intentionally much larger than the 100 nm boundary of the EU nanomaterial definition, but the TiO2 pigment manufacturing processes results in a finite nanoscale content fraction. This optically inefficient nanoscale fraction needs to be quantified in line with EU regulations. In this paper, we describe the measurement procedures used for product quality assurance by three TiO2 manufacturing companies and present number-based primary particle size distributions (PSDs) obtained in a round-robin study performed on five anatase pigments fabricated by means of sulfate processes in different plants and commonly used worldwide in food, feed, pharmaceutical and cosmetic applications. The PSDs measured by the three titanium dioxide manufacturers based on electron micrographs are in excellent agreement with one another but differ significantly from those published elsewhere. Importantly, in some cases, the PSDs result in a different regulatory classification for some of the samples tested. The electron microscopy results published here are supported by results from other complementary methods including surface area measurements. It is the intention of this publication to contribute to an ongoing discussion on size measurements of TiO2 pigments and other particulate materials and advance the development of widely acceptable, precise, and reproducible measurement protocols for measuring the number-based PSDs of particulate products in the size range of TiO2 pigments.
Keywords: electron microscopy; nanomaterials definition; number-based; particle sizing; primary particles